Relationship between myometrial thickness and latency interval of pregnancy after preterm premature rupture of membranes - Nossair, Wael S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Preterm premature rupture of membranes (PPROM) increases the risk of prematurity and leads to a number of other perinatal and neonatal complications. Prolonged latency interval increases probability of complications in mothers with PPROM. The aim of this study was to assess the relationship between the myometrial thickness and the length of latency interval after PPROM. Methods: This study included 62 pregnant women admitted due to spontaneous PPROM from 26 to 37 weeks gestational age. All selected cases were subjected to full medical history, full clinical examination, laboratory investigations, and ultrasound evaluation with measurement of myometrium thickness at lower uterine segment and uterine fundus, measurement of amniotic fluid index. Results: A total 32 (51.7%) of our patients had latency interval <1 week while the rest of patients had latency interval ≥1 week with mean latency interval value was 5.45±2.4 days. Sonographic evaluation of the myometrial thickness showed that the mean thickness at lower uterine segment was 6.6±1.26 mm and at fundus was 6.1±1.28 mm. we found that at cut off point ≥6.9 mm lower uterine segment myometrial thickness had 87.5% sensitivity and 93.3% specificity in prediction of latency interval≥1 week, while at cut off point≥6.4 mm uterine fundus myometrial thickness had 81.3% sensitivity and 63.3% specificity in prediction of latency interval more than 1 week. Conclusions: Sonographic evaluation of myometrial thickness appears to be helpful in prediction of latency interval in PPROM.